Investasi Asing dalam Industri Pariwisata Bali: Sebuah Pandangan Terkait Praktik New Imperialism Bagi Kearifan Lokal - Maharani, Ida Ayu Galih Pramesti; Priadarsini, Ni Wayan Rainy (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
Foreign investment has a significant role in the development of the tourism industry in Bali and contributes to local economic growth. However, the dominance of foreign capital can pose challenges to the existence of local wisdom, economic dependence, and exploitation of local resources. This paper examines foreign investment in Bali’s tourism industry through the perspective of new imperialism using a descriptive qualitative approach. This research shows that there are still foreign investment practices that are not accordance with local wisdom values, but only concerned with profit expansion. This can cause cultural degradation and socio-economic inequality, especially for local Balinese people. With this, concrete steps are needed in the form of collaboration between the government, local communities, and foreign investors to be able to create sustainable tourism development and maintain local traditions.